Working Capital Management on Firms' Profitability: with special reference to manufacturing companies listed in Colombo Stock Exchange (CSE) - Fernando, J.M.R.; Fernando, P.N.D. (University of Kelaniya, 2008)
Short term financing (working capital management) is an important component of corporate finance because it directly affects both liquidity and profitability of the company. Raheman and Nasr, (2007) observed that there is a significant negative relationship between working capital (average collection period, inventory turnover in days, average payment period and cash conversion cycle) and profitability of the firms listed on Karachi Stock Exchange. Pedro Juan and Pedro Martinez (2004) found a significant relationship between SMEs' profitability and the numbers of days account receivables and days of inventory. Objective of this study is to identify the relationship between working capital management and company profitability of the manufacturing companies listed in the Colombo Stock Exchange ( CSE) in order to help Sri Lankan manufacturing companies to manage its working capital more efficiently. Secondary data relating to fifteen companies from 2001 to 2005 is considered for the analysis. Pearson's correlation analysis and regression analysis are used for the data analysis. Number of days accounts receivable, Number of days accounts payable, inventory turnover in days, and cash conversion cycle are the independent variables considered in this study. Sales growth rate, fixed assets to total assets also used as control variables. The results show that there is a strong negative relationship between variables of the working capital management (Number of days accounts receivable, Number of days accounts payable and inventory turnover in days) and profitability of the firm. It means that as the cash conversion cycle increases it will lead to decrease profitability of the firm. Further it revealed that there is a significant negative relationship between liquidity and profitability. These results will be beneficial for the managers to make their short term financing decisions more efficiently.
Keywords: Working Capital Management, Profitability, Cash Conversion Cycle, Inventory Turnover.